The Relationship Between Childhood Trauma, Social Adjustment, and Self-Compassion Based on the Mediating Role of Emotional Schemas in Adolescents with Risky Behaviors - Dabiri, Solmaz; Ebrahimi Moghaddam, Hossein; Babakhani, Narges (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The aim of this study was to investigate the relationship between childhood trauma and social adjustment and self-compassion based on the mediating role of emotional schemas in adolescents with risky behaviors. Materials and Methods: This research employed a descriptive-analytical correlational design. The statistical population included all adolescents with risky behaviors who had referred to welfare-affiliated counseling centers, psychological counseling centers, and neighborhood centers in Tehran during 2024–2025. A total of 324 individuals were selected through convenience sampling based on the minimum sample size calculation for structural equation modeling. Data collection instruments included the Social Adjustment Scale (Bell, 1962), the Self-Compassion Scale (Neff et al., 2003), the Childhood Trauma Questionnaire (Bernstein et al., 2003), and the Emotional Schema Scale (Leahy, 2007). The validity of the questionnaires was confirmed through content and construct validity (convergent and divergent), and reliability was assessed via Cronbach’s alpha, composite reliability, and McDonald’s omega coefficients. Data analysis was conducted using descriptive statistics (demographic and variable descriptions) and inferential statistics (structural equation modeling) with SPSS-v27 and Smart PLS-v3 software. Findings: The results indicated that childhood trauma had a significant and negative indirect effect on social adjustment through emotional schemas (β = -0.481, p < .001). Likewise, childhood trauma had a significant and negative indirect effect on self-compassion through emotional schemas (β = -0.377, p < .001). Conclusion: The study demonstrated that both childhood trauma and emotional schemas directly influence social adjustment and self-compassion in adolescents with risky behaviors. Furthermore, childhood trauma indirectly affects these variables through emotional schemas. The overall conclusion suggests that managing emotions, addressing childhood trauma, and strengthening self-compassion may help reduce risky behaviors and improve adolescents’ mental health. The findings highlight the necessity of psychological and social interventions to support at-risk adolescents.